KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN: SEBUAH ANALISIS EMPIRIS - ketut juniati; I Nyoman Gede Arya Diatmika (Universitas Prof.Hazairin,SH Bengkulu, 2026)
This study aims to analyze the influence of auditor competence and workload on the auditor's ability to detect fraud, with professional skepticism as a mediating variable. This study specifically examines how these factors influence the effectiveness of fraud detection among auditors working at Public Accounting Firms (KAP) in Bali.The research method used was quantitative, involving 70 auditors selected using purposive sampling from KAPs registered in the IAPI directory in 2025. Primary data was obtained through questionnaires, while secondary data was obtained from previous empirical studies. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the direct and indirect effects between variables. The results show that auditor competence has a positive and significant effect on professional skepticism and the ability to detect fraud. Professional skepticism also has a significant positive effect on the auditor's ability to detect fraud. Conversely, workload has a significant negative effect on both professional skepticism and the ability to detect fraud. Furthermore, auditor competence has a significant positive effect on the ability to detect fraud through professional skepticism, while workload has a significant negative effect on the ability to detect fraud through professional skepticism. Overall, this study concludes that enhancing auditor competence and strengthening professional skepticism are crucial for enhancing auditors' ability to detect fraud. Meanwhile, optimal workload management is necessary to prevent auditor skepticism and performance degradation. These findings highlight the importance of balancing workload, enhancing competence, and applying professional skepticism to improve audit quality and fraud detection effectiveness.